2005
DOI: 10.1016/j.pcad.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Pneumoniae and Atherosclerosis: From Koch Postulates to Clinical Trials

Abstract: Atherosclerosis is increasingly viewed as an inflammatory process. A number of infectious agents have been implicated in the pathogenesis of coronary artery disease. Chlamydia pneumoniae has been the most popular and well-studied of these pathogens. It is difficult to prove a causal relationship which requires the fulfillment of Koch's postulates, first developed in the late 1800s, to establish an infectious agent as the cause of a disease process. This paper reviews the evidence for and against Chlamydia pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…In addition to endogenously generated autoantigens, T cell may recognize antigens produced by infectious organisms that reside in plaques. Perhaps the most extensively studied microbe putatively implicated in the pathogenesis of atherosclerosis in Chlamydia pneumoniae (Cpn) 16. T cells specific for CpN Hsp65 have been isolated from human lesions, and CpN HSP65 has been detected in the majority of human lesions analyzed 17,18.…”
Section: Candidate Atherosclerosis-related T Cell Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to endogenously generated autoantigens, T cell may recognize antigens produced by infectious organisms that reside in plaques. Perhaps the most extensively studied microbe putatively implicated in the pathogenesis of atherosclerosis in Chlamydia pneumoniae (Cpn) 16. T cells specific for CpN Hsp65 have been isolated from human lesions, and CpN HSP65 has been detected in the majority of human lesions analyzed 17,18.…”
Section: Candidate Atherosclerosis-related T Cell Antigensmentioning
confidence: 99%
“…T cells specific for CpN Hsp65 have been isolated from human lesions, and CpN HSP65 has been detected in the majority of human lesions analyzed 17,18. Nonetheless, studies have failed to show that antibiotic therapy reduces atherosclerosis-related clinical events in patients at risk 16,18. Another candidate antigens that has also been implicated in the pathogenesis of atherosclerosis is β-glycoprotein Ib (β-GPI) 1921, which is expressed by platelets.…”
Section: Candidate Atherosclerosis-related T Cell Antigensmentioning
confidence: 99%
“…It has been reported that C. pneumoniae infection is associated with some chronic diseases, including atherosclerosis and neuronal diseases (Balin et al 1998;Sriram et al 1999;Stratton and Sriram 2003;Belland et al 2004;Liu and Waters 2005;Kaperonis et al 2006;Stratton and Wheldon 2006). The diverse function of immune cells results in their playing a central role in the development of such chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicate that this bacterium may contribute to the pathogenesis of chronic inflammatory diseases, including atherosclerosis, as demonstrated seroepidemiologically and pathologically (Saikku et al 1988;Kuo et al 1993;Jackson et al 1997;Belland et al 2004;Campbell and Kuo 2004;Liu and Waters 2005). However, the pathophysiological role of C. pneumoniae infection in the development of chronic inflammatory diseases is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they were able to demonstrate that if low grade inflammatory response as measured by CRP was taken into consideration then the coronary risk was almost doubled [52]. Since then a number of groups have investigated the association between C.pneumoniae seropositivity and coronary risk [53]. In 1997, Danesh et al published a meta-analysis of 18 seroepidemiological studies [54].…”
Section: A) Chlamydia Pneumoniaementioning
confidence: 99%